The Pox Lover : An Activist's Decade in New York and Paris - D'Adesky, Anne-Christine; Project Muse. (Madison, Wisconsin : The University of Wisconsin Press, 2017)
The Pox Lover is a personal history of the turbulent 1990s in New York City and Paris by a pioneering American AIDS journalist, lesbian activist, and daughter of French-Haitian elites. In an account that is by turns searing, hectic, and funny, Anne-christine d'Adesky remembers 'the poxed generation' of AIDS -- their lives, their battles, and their determination to find love and make art in the heartbreaking years before lifesaving protease drugs arrived. D'Adesky takes us through a fast-changing East Village: squatter protests and civil disobedience lead to all-night drag and art-dance parties, the fun-loving Lesbian Avengers organize dyke marches, and the protest group ACT UP stages public funerals. Traveling as a journalist to Paris, an insomniac d'Adesky trolls the Seine, encountering waves of exiles fleeing violence in the Balkans, Haiti, and Rwanda. As the last of the French Nazis stand trial and the new National Front rises in the polls, d'Adesky digs into her aristocratic family's roots in Vichy France and colonial Haiti. This is a testament with a message for every generation: grab at life and love, connect with others, fight for justice, keep despair at bay, and remember.
Description based on print version record.
Keywords: D'Adesky, Anne-Christine.; D'Adesky, Anne-Christine; D'Adesky, Anne-Christine.; Women political activists; Journalists; AIDS activists; Femmes activistes -- Biographies; Dissent and Disputes; Acquired Immunodeficiency Syndrome -- history; Journalists -- Biography; AIDS activists -- Biography; Women political activists -- Biography; Autobiographies; Autobiographies; Biographies; Autobiographies; Autobiography; Electronic books